The Influence of Injectable Platelet-Rich Fibrin on the Clinical Parameters and the Levels of MMP-8 in the GCF in Non-Surgical Treatment of Periodontitis—Randomized Trial - Anna Skurska; Marek Chwiedosik; Anna Justyna Milewska; Robert Milewski; Michał Pawłowski; Jennifer Alberichi; Violetta Dymicka-Piekarska; Martina Stefanini (Journal of Functional Biomaterials)
Background: This study evaluates non-surgical therapy combined with injectable platelet-rich fibrin (i-PRF) on the clinical parameters and the levels of matrix metalloproteinase-8 (MMP-8) in the gingival crevicular fluid (GCF) in patients with periodontitis. Methods: Forty subjects diagnosed with periodontitis were randomly divided into two groups. In the test group, scaling and root planing (SRP) was performed with the subsequent application of i-PRF into periodontal pockets, while in the control group SRP was performed alone. Clinical examination was performed before and 1, 3 and 6 months after treatment. For MMP-8 level determination, the ELISA method was used. Results: In both groups, a statistically significant reduction in full mouth probing depth (FMPD), full mouth clinical attachment level (FMCAL), full mouth bleeding on probing (FMBOP), full mouth plaque index (FMPI) and full mouth marginal bleeding index FMMBI (p < 0.001) was observed. In the test group, the reduction in FMPD and FMBOP was statistically significantly greater than in the control group (p = 0.049 and p < 0.001, respectively). A significantly greater reduction of probing depth (PD) and clinical attachment level (CAL) in pockets > 5 mm between baseline and examination after 3 and 6 months was noted in the test group. The level of MMP-8 was statistically significantly reduced in both groups (p = 0.007 and p = 0.009). Conclusions: SRP significantly improves the clinical parameters and reduces MMP-8 levels in patients with periodontitis. Addition of i-PRF may further enhance the positive effects of periodontal treatment on clinical parameters, without significant influence on MMP-8 levels. The results of the research require confirmation in a more homogeneous group, taking into account the elimination of the specified limitations.